(untitled) (Fiep Bulletin - online, 2013)
This article is the result of the extension project conducted under the Federal Institute of Education, Science and Technology of Alagoas - Campus Maragogi (IFAL), with implementation in State Baptist College Acioli in the same county. Aiming to map the risk factors in adolescents aged 14 to 18 years old in the city of Maragogi. This is a quantitative descriptive type where students were initially assessed at the Federal Institute of Alagoas/Campus Margogi - who joined in 2010 and soon after with Acioli Baptist School students, using assessment as a method using biometric balance, estadiômentro, tape measure and caliper. Were evaluated, school students and Municipal Federal Institute of Alagoas/Maragogi campus where we had 73 girls with a mean of 16 years and 87 boys aged 17 years. Both genders, are not running any coronary risk due to BMI and WHR were within normal according to World Health Organization